Kalevala through Translation: Continuity, Rewriting and Appropriation of an Epic - Plourde, Éric (Meta, 2006)
The Kalevala, the national epic of the Finnish people, published in the 19th century and created by E. Lönnrot from songs collected in the Karelian countryside (Northwestern Russia), is the result of a long process of rewriting. This process has manifested itself through successive retranslations in various languages and through certain strategies favored by the epic’s translators. Recent translations reflect a tendency to appropriate the epic through the use of a vocabulary and poetic style that are specific to the culture of the translator. For example, verse translations in Tamil are structured in the manner of folk epics of Southern India; while in the French verse translation the translator has made abundant use of archaisms and neologisms. Le Kalevala, l’épopée nationale des Finlandais publiée au xixe siècle et créée par E. Lönnrot à partir de chants recueillis dans la campagne carélienne (dans le nord-ouest de la Russie), est le fruit d’un long processus de réécriture, processus qui se reflète à la fois dans l’existence de plusieurs traductions dans une même langue de l’épopée finlandaise et dans l’approche privilégiée par les traducteurs. De plus, la tendance récente montre une appropriation de l’épopée par l’utilisation d’un vocabulaire particulier, d’un style de poésie spécifique à la culture traduisante. Les versions métriques en tamoul sont structurées à la manière des anciennes épopées populaires du sud de l’Inde la version métrique française est aussi teintée d’archaïsme surtout lexicologique, doublé d’un recours fréquent à la néologie de la part du traducteur.